New insight into the controlling factors of differences in carbonate buried-hills driven by tectonic activity: a case study of the Weixinan Sag, Beibuwan Basin, China - Yanying Li; Kongyou Wu; Jia Zhong; Yannan Du; Jinyou Wang (Journal of Petroleum Exploration and Production Technology)
Abstract As the main field for crude oil exploration in the western of the South China Sea, the Weixinan Sag, Beibuwan Basin, has discovered multiple hydrocarbon-bearing structures. Carboniferous carbonate buried-hills in the Weixinan Sag, as a new field for increasing oil reserves and production, have enormous potential for exploration. Due to the influence of karstification, carbonate buried-hill reservoirs exhibit strong heterogeneity and rapid changes in physical properties, making the exploration of effective reservoirs more difficult. In this study, drilling cores and resistivity imaging logging data were employed to investigate the petrological characteristics and fracture development patterns of buried-hill reservoirs. By processing and calculating well logging curves, the development characteristics and vertical distribution patterns of karst in buried-hill reservoirs can be effectively displayed. Based on this, divide karst facies zones, measure karst thickness, and analyze their distribution patterns. The results indicate that tectonic activity is the main controlling factor for the karst differences in carbonate buried-hills in the Weixinan sag. the carbonate buried-hills karst in the No. 1 and No. 2 fault zones has characteristics of vertical zoning, plane partitions, and multiple phases. The buried-hills in the No. 1 fault zone have more karst stages and effective karst storage space than the buried-hills in the No. 2 fault zone. We propose four karst types under the control of tectonic activities, and establish a development model for the karst in the Weixinan Sag buried-hills. This study provides significant guidance for the development and reservoir prediction for similarly carbonate buried karst hills.